2013
DOI: 10.1111/1574-6968.12080
|View full text |Cite
|
Sign up to set email alerts
|

Different secreted phosphatase activities inLeishmania amazonensis

Abstract: Leishmania has strong acid phosphatase activity on the external surface of the plasma membrane and secreted into the extracellular milieu. Secreted acid phosphatase (sAcP), which is the most abundant secreted protein of Leishmania, is also a virulence factor that plays a role in vertebrate infection and survival in sand flies. In this study, we characterized the secreted phosphatase activities in Leishmania amazonensis. Both acidic and alkaline secreted phosphatase activities were observed with β-glycerophosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 48 publications
(67 reference statements)
1
31
0
Order By: Relevance
“…Phosphatases can be characterized on the basis of their location in the cell, which can be intracellular i.e., secreted to the extracellular medium from the cell or membrane bound i.e., associated to plasma membrane [34, 35]. Phosphatases were found to be widely distributed throughout the cell (cytoplasm, mitochondria, nucleus, extracellular, plasma membrane, etc.).…”
Section: Resultsmentioning
confidence: 99%
“…Phosphatases can be characterized on the basis of their location in the cell, which can be intracellular i.e., secreted to the extracellular medium from the cell or membrane bound i.e., associated to plasma membrane [34, 35]. Phosphatases were found to be widely distributed throughout the cell (cytoplasm, mitochondria, nucleus, extracellular, plasma membrane, etc.).…”
Section: Resultsmentioning
confidence: 99%
“…By combining our experimental results with sequence similarity searches and alignments of PLD_SC with other enzymes, we have identified other species of enzymes with similar amino acid sequence to that of PLD_SC that may also be inhibited by this class of molecules and that have physiological relevance as a drug target. The literature searches revealed that several of the potential new targets identified are also active or activated as membrane associated enzymes (like PLD_SC) at both the cell membrane and as part of intercellular vesicle transport pathways . Previous studies with these enzymes provides compelling functional evidence that kinetic and binding studies done with PLD_SC (Table , Figures.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphatases can also be classifi ed according to their subcellular location, which can be intracellular (Andrews and Stark 2000 ;Zhan et al 2000 ); secreted from the cell to extracellular medium (Rodrigues et al 1999 ;Dutra et al 2001 ;Fernandes et al 2013 ); or even membrane-bound enzymes, which may be associated to plasma membranes . In this context, the ecto-phosphatases are surface membrane-bound proteins, whose active site faces the extracellular medium (Furuya et al 1998 ).…”
Section: Subcellular Localizationmentioning
confidence: 99%
“…Membrane-bound and secreted kinase and phosphatase activities are directly involved with the degree of virulence in pathogenic microorganisms (Cunningham 2002 ;Fernandes et al 2013 ). In L. donovani , it was observed that ecto-phosphatase activity was signifi cantly higher in virulent strains than in avirulent strains, suggesting that ecto-phosphatase may be considered as virulence marker (Singla et al 1992 ).…”
Section: Ecto-phosphatases As Virulence Markers: Possible Roles In Admentioning
confidence: 99%